Preparation of mg-si and nitrogen-doped graphene nanocomposites for use as lithium-ion anode - Parinya Jinai (2020)
© 2020 Trans Tech Publications Ltd, Switzerland. Si and Mg are good candidates for anode lithium-ion batteries because Si and Mg have high theoretical capacity of 4200 mAh g-1 and 994 mAh g-1, respectively. However, these elements generate high-volume expansion during the charge-discharge process, which can cause the electrode to crack after being used for a few cycles. To solve this problem, the active materials are prepared in a nanosize and composited with a 2D-sheet of nitrogen-doped graphene, as the high mechanical stability and flexibility of nitrogen-doped graphene can support the volume expansion. Preparation of Si-Mg and nitrogen-doped graphene includes two steps. First, the reduction of Mg2+ ions with NaBH4 in ethylene glycol solution and reflux at 350-400 °C for 3 hr and Si nanoparticles, which were prepared by magnesiothermic reduction, was conducted. Second, Si and Mg nanoparticles and nitrogen-doped graphene were mixed in ethylene glycol solution and then collected by centrifugation. The obtained Si-Mg nanocomposite particles were well distributed on the nitrogen-doped graphene. The phases were indexed as Si, Mg and nitrogen-doped graphene. The particle sizes were small (approx 21-56 nm) with good dispersion on the nitrogen-doped graphene which observed by transmission electron microscopy and scanning electron microscopy techniques. Energy dispersive spectrometry results confirmed the existence of Si-Mg. Therefore, Si-Mg and nitrogen-doped graphene nanocomposite materials are expected to contain promising properties that can be used as high-performance anode materials in lithium-ion batteries in the future.